Ambivalent desires: the "New Woman" between social modernization and modern writing - Köhler, Angelika (American studies, 2004)
The study explores the phenomenon of the "New Woman" as a most controversial construct of turn-of-the-19th-century US-American culture. Images of the "New Woman" shaped the discourses of mainstream press as well as those of leading feminists of the time. Against the background of the processes of social modernization, the multifaceted versions of this female image are investigated as productions und reproductions of women's "ambivalent desires" to articulate their female awareness of modernity by rereading texts written by male and female so-called popular and canonical authors and by discussing selected contemporary discourses of journalism. The analysis sets out to explore the centrality of gender to the development of forms of modern US-American writing conceptualized as a network of diverse yet mutually interacting gendered discourses
https://katalog.adlr.link/Record/0-1610250435